Alpine skiing technique - practical knowledge and scientific analysis - Loland, S. (Science and Skiing IV, 2008)
Imagine a skilled downhill skier carving turns in a steep descent. The skier balances on a thin steel edge at speeds more than 100 kilometres per hour. From the neuromuscular activity at the local level via the interaction through skis and poles with a constantly changing surface to the very experiential Gestalt of a well executed run, this is a highly complex movement pattern. How are we to understand good alpine skiing technique? What are human movement techniques all about? In the first part of this essay l will depart from the practical insights of technique among expert skiers and coaches and examine if, and possibly in what way, their understandings can be exposed to the systematic and critical tests of movement analysis. The second part explores an alternative route of investigation to better grasp ideas that are difficult to analyze, such as the rhythmic character of good skiing. In the concluding comments, it is speculated as to whether we can expect a merging of apparently contradictory and alternative perspectives on movement technique in the future.